Measuring ODL effectiveness: A comparative analysis of student performance in independent landscape design / Suriati Ahmad ... [et al.] - Ahmad, Suriati; Mohd Hussain, Nur Huzeima; Md Sakip, Siti Rasidah; Mansor, Azran; Bahaluddin, Azrul; Ilias, Nur Hanim (2021)
The outbreak of Covid-19 pandemic that hit Malaysia from February 2020 has indirectly transformed the world educational learning environment, from face to face learning to massive online platforms. As aligned to the Educational 5.0 @ UiTM that embraces values and future progressive thinking, the application of ODL (online distance learning) throughout this pandemic phase has seen a positive and progressive move towards student performance undertaking Independent Landscape Design course. This design-based syllabus that requires a complete landscape design process is synergised to a face to face learning environment. However due to this outbreak, the application of ODL has demonstrated the changes of delivery approach (from traditional to online learning), seeing how MOOC platform (massive open online courses) able to stand as the leading channel that aided landscape design students in performing and delivering their understanding on landscape design process, design approaches and technical drawings in completing their final project. Acknowledging the shift of design-based delivery approach, this paper will further discuss measuring student performance throughout the ODL implementation. These analytical findings further reveal the factors that bestow student performance despite the reality behind the success of this new teaching strategy that is achievable for landscape architecture design students.